THE EFFECT OF ADVERTISING EXPOSURE OF DIGITAL BANK, USER EXPERIENCE ON M-BANKING, AND USER’S BRAND AWARENESS TOWARD THE INTENTION TO CREATE AN ACCOUNT - Tan Faizal Rachman; Tandiyo Pradekso; Yanuar Luqman (Interaksi Online, 2022)
The purpose of this research is to analyze the effect of Digital Bank’s advertisement exposure, User Experience on M-Banking, and digital bank brand awareness toward the intention to create an account of digital bank. The new phenomenon of the mass acquisition of small banks and remodeling maneuver thus the cooperation with overseas bank during the unprecedented wave of pandemic has become the issue. Digital bank, which bank that fully operated within the digital environment has become the trend among corporations. Apart from advantages these banks have to offer, the digital era is coming, and brought its disadvantages along the way. Cybercrime, which highly related to the digital world, and digital bank, has stiffen its position as the 2nd highest reported case in Indonesia. Moreover, with the constant enhancement of MBanking, people are now allowed to engage in the easiest transactional activity as possible. On the other hand, people are now confronted with options, whether to stay with M-Banking, or opt the Digitallyoperated bank. These situation however, are taken as efficiently as possible by the digital banks corporation to create such awareness, through massive concert, exhibition, collaboration, sponsorship, and advertisement. This research is done by collecting 108 respondents and referred to primary data. The statistical analysis implemented in this research is simple linear regression, by analyzing the effect of advertising exposure of digital bank toward intention to create an account, user experience of M-Banking toward the intention to create an account, and digital bank brand awareness toward the intention to create an account. The results retracted from the statistical measurement concluded that simple linear regression test on the advertising exposure of digital bank toward intention to create an account, it showssignificance result of 0.621, user experience of M-banking toward the intention to create an account it yielded significance result of 0.382, brand awareness of digital bank on the intention to create an account, it returned with the significance result of 0.636 which means that simple linear regression of user experience on M-Banking and, Digital bank brand awareness does not show a significant effect, resulting on the statistical result all above 0.05. Therefore, three of these variables does not affect the intention to create an account of digital bank.